Integration of Massive Open Online Course (MOOC) in Conventional Teaching and Learning for Fixed Prosthodontics - A Case Study - Abdul Hamid, Nor Faharina; Ahmad, Rohana; Lim, Tong Wah; Kamar Affendi, Nur Hafizah; Tengku Mohd Ariff, Tengku Fazrina; Mahmud, Melati; Ab Ghani, Siti Mariam (Journal of Dentistry Indonesia, 2023)
The potential for Massive Open Online Courses (MOOCs) in clinical dentistry remains vague and inadequately explored. Objectives: The study aims to obtain insight into the development of MOOCs in Fixed Partial Dental Prostheses (FPDPs) and to assess students’ learning preferences, module quality, and interface usability. Methods: The MOOCs was created by seven academicians with prosthodontic backgrounds. After completing the MOOCs and three complementary online discussion sessions, the students (n = 89) were invited to participate in an online survey. SPSS version 23 was used to calculate the frequency, percentage, mean, and standard deviation of categorical data (SD). Results: A total of 84.1% of students completed the survey. Six modules with five different FPDPs topics and a single implant topic were created for this MOOCs, which consists teaching and practical modules. 94.6% of respondents agreed that MOOCs can be used to supplement traditional T&L, with 64.9% preferring MOOCs to traditional classrooms. The majority of the items received a high mean score above 4.00, indicating that the majority of respondents were satisfied with the developed MOOC’s course content, usability, and interface. Conclusion: The majority of respondents agreed that the overall course content is well-organized and expressed positive feedback on integrating MOOCs into traditional classrooms.